Optimalisasi Sertifikasi Guru: Jalan menuju Profesionalisme dan Kesejahteraan Pendidikan - Fachlevi, Muhammad Rieza; Faribi, Fadhilah Al; Ajahari, Ajahari (TSAQOFAH, 2025)
Teacher certification is an official recognition of professional status aimed at enhancing teachers’ competencies and well-being, as well as strengthening the overall quality of education. This study systematically analyzes literature on the impact of teacher certification on analytical capacity, professional skills, and well-being. A systematic literature review (SLR) was conducted on ten relevant scholarly articles. The review findings indicate that certification positively contributes to improving teachers' professional capacity, including teaching skills and well-being through financial compensation. However, the study also identifies implementation challenges such as unequal distribution of certification allowances, misaligned financial incentives, and limited access to ongoing training. The research concludes that teacher certification holds significant potential to improve education quality, provided it is supported by comprehensive policies, continuous professional development, and adaptive growth strategies. These findings underscore the need for a holistic approach in the formulation and implementation of certification programs to ensure the optimal achievement of educational objectives.